Anti-Oxidation Electrochemical Sensor Based on Nanocomposites for Sensitive Detection of Nitrite. Issue 1 (29th January 2021) - Chu, Guanglei; Huang, Jingcheng; Yin, Jiaqi; Guo, Yemin; Sun, Xia; Li, Ming; Zhang, Yanyan; Wang, Xiangyou
Abstract : Copper nanoparticles (Cu NPs) have good catalytic performance, but they are easy to be oxidized in the air, which greatly limits their practical application. In this paper, a novel anti-oxidation nitrite electrochemical sensor based on carboxymethylcellulose sodium functionalized reduced graphene oxide-copper nanoparticles (RGO-CMC@Cu NPs) was successfully prepared. Utilizing the high hydrophilia characteristic of CMC, the surface of Cu NPs was coated with an anti-oxidation film to reduce the oxidation rate of copper. At the same time, CMC was used to modify RGO that effectively increased the dispersion ability of RGO in aqueous solution. The prepared nanocomposites were characterized by Transmission Electron Microscope (TEM) and Energy Dispersive Spectroscopy (EDS). Under the optimal conditions, the fabricated sensor based on RGO-CMC@Cu NPs was used to detect nitrite by chronoamperometry. The linear detection ranges of the sensor were 1–15, 000 μ M and 15, 000–41, 000 μ M with limit of detection (LOD) of 0.05 μ M (S/N = 3), and the sensitivities were 0.171 μ A· μ M −1 ·cm −2 and 0.108 μ A· μ M −1 ·cm −2, respectively. In the stability test, the sensor was able to retain 91.1% of its initial sensitivity after 25 days of exposure to air.